2021
DOI: 10.1097/opx.0000000000001776
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Provider Perspectives on Glaucoma Treatment Adherence: A Delphi Study in Urban Alabama

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Until such improvements are made, providers should maintain awareness of the negative impact of the pandemic on adherence and highlight this during clinic visits. The patient-provider relationship has previously been described as a facilitator of good adherence, 38 and is a promising vehicle for identifying barriers as they arise in patients, as well as for developing individualized solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Until such improvements are made, providers should maintain awareness of the negative impact of the pandemic on adherence and highlight this during clinic visits. The patient-provider relationship has previously been described as a facilitator of good adherence, 38 and is a promising vehicle for identifying barriers as they arise in patients, as well as for developing individualized solutions.…”
Section: Discussionmentioning
confidence: 99%
“…This may strengthen and lengthen the patient-provider relationship, which has also been associated with higher adherence ( 29 ). The patient-provider relationship has been identified as a facilitator of good adherence ( 30 ), and research has shown that non-adherent patients were less likely to believe that their eye doctors spent sufficient time talking with them about their eye condition ( 31 ). Increased focus on patient education regarding the clinical impact of poor adherence may also help to increase engagement in eye care and improve adherence to prescribed medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Forgetfulness is a common reason for nonadherence [21,94,95], and true cognitive impairment is the most serious form thereof. Dementia is a risk factor for poor adherence to all therapies [96], including glaucoma therapy [77,97], as well as a risk factor for general self-neglect [98].…”
Section: Cognitive Limitationsmentioning
confidence: 99%